(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: to determine the influence of Classical exercises on the distribution of attention of schoolchildren. Method: the pedagogical experiment was conducted during the academic year. It was attended by students aged 9-10 years (40 people). Coordination abilities were determined by the “Shuttle Run” test, and the distribution of students’ attention by the “Different counting” method. Statistical processing of the results was carried out according to the Bio-Stat program and the T-student was calculated. Results: after the experiment, the indicators in the control group improved by 2.9% (p>0.05) - shuttle running, and the distribution of attention from 36.1±2.4 to 32.9±3.4 (p>0.05). In the experimental group, shuttle running significantly improved by 14.1% (p<0.05), and the distribution of attention improved from 9.9±0.5 to 8.5±0.4 (p<0.05). Such data indicate the effective effect of Classical exercises on the indicators of the distribution of students’ attention. Conclusion: if students of 9-10 years of age in physical education classes will perform the Classics exercise, then the indicators of coordination abilities and the distribution of children’s attention will significantly improve. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 604-611